2009
DOI: 10.1186/1476-9255-6-21
|View full text |Cite
|
Sign up to set email alerts
|

Is inflammation a consequence of extracellular hyperosmolarity?

Abstract: BackgroundThere are several reports suggesting that hyperosmolarity induces inflammation. We recently showed that Dextran Sodium Sulfate causes inflammatory bowel disease due to hyperosmolarity. The aim of this study was to confirm the link between hyperosmolarity and inflammation by assessing osmolarity values in vivo during inflammation, compare the inflammatory potential of different osmotic agents and finally study the long-term consequences of hyperosmolarity on cell fate.MethodsOsmotic pressures were mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
93
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(101 citation statements)
references
References 45 publications
(26 reference statements)
5
93
0
Order By: Relevance
“…It has been previously hypothesized that DSS contributes to induction of colitis via a hyperosmotic stress response (50,53). Here, we provide direct evidence that DSS increases the osmolarity of extracellular fluid and that osmoadaptive genes are upregulated in response to DSS-induced extracellular osmolarities of 395 mosM.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…It has been previously hypothesized that DSS contributes to induction of colitis via a hyperosmotic stress response (50,53). Here, we provide direct evidence that DSS increases the osmolarity of extracellular fluid and that osmoadaptive genes are upregulated in response to DSS-induced extracellular osmolarities of 395 mosM.…”
Section: Discussionsupporting
confidence: 54%
“…However, the signaling pathway leading from DSS treatment to iNOS induction via PKR may not be the same as detailed above in the hyperosmotic stress response. Although DSS has been suggested to increase the extracellular osmolarity (50,53), the molecular mechanisms of the cellular response to DSS are not well studied. In order to investigate the hypothesis that DSS induces a hyperosmotic stress response sufficient to cause colitis, we used a culture model of MEF cells treated directly with DSS as a hyperosmotic agent.…”
Section: Amplification Of Inos Has Proapoptotic Effects During Hyperomentioning
confidence: 99%
“…LD formation is not an event relevant only for our cellular model, but could have implications in other systems as well. Schwartz et al ( 37 ) revealed that pathogen-related infl ammatory reaction increases the osmolarity of infl ammatory fl uids. Given that infl ammation is an essential cellular response to all stress inducers, its intimate connection with HO becomes an important issue in contexts different from that of the corneal surface or DES.…”
Section: Discussionmentioning
confidence: 99%
“…Just as there is now considerable ONCOLOGY REPORTS 23: 1407-1416, 2010 A combination of alpha lipoic acid and calcium hydroxycitrate is efficient against mouse cancer models: Preliminary results interest in the role of the glycolytic phenotype as a key target for the development of effective drugs for cancer, the inflammatory response has also been recognized as a potential target (12,13). Our laboratory has in the past few years investigated the role of hyperosmolarity as a cause of inflammation and its potential link to cancer (14)(15)(16) and most recently showed that the inhalation of carbon dioxide, a product of cellular respiration, was able to induce inflammation of the lung (17). As a consequence, focusing on metabolic changes involving glucose metabolism that characterize cancer cells appeared to us to be a logical extension of our work in the area of inflammation.…”
Section: Introductionmentioning
confidence: 99%